Cropland Net Ecosystem Exchange Estimation for the Inland Pampas (Argentina) Using EVI, Land Cover Maps, and Eddy Covariance Fluxes - Marconato, Ulises; Fernández, Roberto J.; Posse, Gabriela (Frontiers in Soil Science, 2022)
Estimations of Net Ecosystem Exchange (NEE) are crucial to assess the carbon sequestration / carbon source capacity of agricultural systems. Although several global models have been built to describe carbon fluxes patterns based on flux-tower data, South-American ecosystems (and croplands in particular) are underrepresented in the databases used to calibrate these models, leading to large uncertainties in regional and global NEE estimation. Despite that almost half of the land surface is used worldwide for agricultural activities, these models still do not include variables related to cropland management. Using enhanced vegetation index (EVI) derived from MODIS imagery (250 m) and monthly CO2 exchange from a 9-year record of an eddy covariance (EC) flux tower in a crop field in the Inland Pampas region, we developed regression models to predict monthly NEE. We tested whether including a term for crop identity/land cover as a categorical variable (maize, soybean, wheat and fallow) could improve model capability in capturing monthly NEE dynamics. NEE measured at the flux tower site was scaled to croplands across the Inland Pampa using crop type maps, from which annual NEE maps were generated for the 2018-2019, 2019-2020 and 2020-2021 agricultural campaigns. The model based solely on EVI showed to be a good predictor of monthly NEE for the study region (r2=0,78), but model adjustment was improved by including a term for crop identity (r2:0,83). A second set of maps was generated taking into account carbon exports during harvest to estimate Net Biome Productivity (NBP) at county level. Crops across the region as a whole acted as a carbon sink during the three studied campaigns, although with highly heterogeneous spatial and temporal patterns. Between 60% and 80% of the carbon sequestered was exported during harvest, a large decrease from the carbon sequestration capacity estimated using just NEE, further decreased if fossil-carbon emissions from agricultural supplies are taken into account. Estimates presented in this study are a first step towards upscaling carbon fluxes at regional scale in a South American cropland area, and could help to improve regional to global estimations of carbon fluxes and refine national GHG inventories.